Investigation of Demodex Prevalence Due to Mask Use After the COVID-19 Pandemic with Cellophane Tape Method - Ahmet Duran Ataş; Berna Baysal Bakay (Türkiye Parazitoloji Dergisi, 2025)
Objective: Demodex species in the family Demodicidae are hair follicle scabies agents. Demodex species are transmitted from person to person through close contact, shared towels, make-up materials, etc. This study was conducted to obtain data on the relationship between mandatory mask use and demodicosis during the Coronavirus disease-2019 (COVID-19) period. Methods: The study included 510 students who used masks in necessary environments since the beginning of the pandemic and participated in the study voluntarily. Cellophane tapes were applied to the relevant areas three times. In addition, both eye lashes were pulled from both eyes and adhered to the cellophane tapes. The samples were examined under light microscope at different magnifications (x10, x40). Results: Demodex folliculorum and Demodex brevis were detected in 38 (7.5%) of 510 students. D. folliculorum was detected in 33 of the positive students and both D. folliculorum and D. brevis were detected in 5 students, 2 of whom were male and 3 of whom were female. Demodex spp. was found in 12 (4.9%) of 245 students who answered “no” to the question “Do you have acne or skin complaints on your face?” and in 26 (9.8%) of 265 students who answered “yes”. While this parameter was statistically significant, the other parameters were not statistically significant. Conclusion: The COVID-19 period has changed people’s lifestyles and habits in many ways. It has made the use of masks obligatory. During mandatory mask use, factors that may increase the presence of Demodex spp. should not be ignored.